2020
DOI: 10.1108/ijbpa-11-2019-0100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of effectiveness of wooden floor finishes in some residential buildings in Lagos, Nigeria

Abstract: PurposeWood is one of the materials that is used for building construction either as structural member or as finishes from ages past to contemporary generation. It is composed of elongated, hollow spindle shaped cells that are arranged parallel to each other along the trunk of a tree. The resistance to water, chemicals, strength properties, appearance and decay rate is dictated by the fibrous cells. The purpose of this paper was to examine the application and use of wooden floor finish (an extract from wood) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Additionally, a qualitative study found that wood flooring is used for aesthetic reasons or for the beauty of the room, and workspaces with natural wood grain look more natural [12]. Wood floor finishes create a sense of spaciousness and add aesthetic value to the interior space of buildings [43]. In a survey, 88% of respondents answered that the color of furniture has a significant impact on our lives [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a qualitative study found that wood flooring is used for aesthetic reasons or for the beauty of the room, and workspaces with natural wood grain look more natural [12]. Wood floor finishes create a sense of spaciousness and add aesthetic value to the interior space of buildings [43]. In a survey, 88% of respondents answered that the color of furniture has a significant impact on our lives [5].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults expressed fear of tile floors, as mentioned earlier, mainly due to the fear of falling associated with tile floors. Wooden floors are considered safe and healthy, with the lowest incidence of household accidents [43]. Healthy older adults take twice as long as young people to get up, while older people in congregate housing take two to three times as long [53].…”
Section: Discussionmentioning
confidence: 99%
“…The influx of Ordinary Portland Cements into the country after independence in 1960 encouraged the use of sandcrete hollow blocks as building materials improved techniques. Research had shown that people spent about 80-90% of their time indoor environment, whether at home or in public buildings (Sujanova et al, 2019) as cited in Nusrat et al (2020) and buttressed by Lebrasseur et al (2019) cited in Folorunso (2020). Given the foregoing, the in-depth study of the thermal performance of sandcrete hollow blocks as a walling material to provide an acceptable indoor thermal comfort for tropical buildings in Lokoja cannot be overemphasized.…”
Section: Sandcrete Hollow Blocks 653mentioning
confidence: 99%